Fewer Dollars, Shrinking Enrollments, Fixed Cost New Financial Dilemma - Saunders, Charles B., Jr. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
In this speech, the author analyzes what should be the proper role of the Federal Government in the financing of public elementary and secondary education. The paper begins with a brief discussion of the financial dilemma the schools face currently; statistics are cited relative to student enrollment, capital costs, teacher salaries, and other operating expenses. The author argues against expanding substantially the federal role in education, and contends that the Federal Government should continue to exercise leadership, through research and demonstration, in areas that involve the national interest. The paper concludes by examining efforts that are being made to stabilize, simplify, consolidate, and equalize current federal educational programs. (Author/DN)
ERIC Note: Paper presented at American Association of School Administrators Annual Convention (106th, Atlantic City, New Jersey, February 22-26, 1974).
Educational level discussed: Elementary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Finance; Educational Legislation; Elementary Education; Enrollment Trends; Federal Aid; Federal Programs; Federal State Relationship; Financial Problems; Government Role; School Support; Secondary Education; Speeches; Federal Role